TuThor: an innovative new training model for video-assisted thoracic surgery. (28th November 2019) - Domhan, Lorenz; Johannink, Jonas; Miller, Johanna; Steger, Volker; Linder, Albert; Kirschniak, Andreas; Wilhelm, Peter
Abstract: : OBJECTIVES: Video-assisted thoracic surgery (VATS) is a complex technique requiring dedicated surgical training. Platforms for such training are scarce and often rely on the use of live animals, which raises ethical concerns. The objective of this study was to develop a box trainer that is dedicated for VATS training and able to reproduce bleeding scenarios. METHODS: The developed Tuebingen Thorax Trainer comprises 5 components that are mounted on a human anatomy-like thoracic cavity containing a porcine organ complex. Any standard thoracoscopic instrument can be used. The organ complex is attached to a perfusion module. We assessed the applicability of the system in four 1-day VATS training courses at the Tuebingen Surgical Training Center. Assessment was performed using a questionnaire handed out to all participants. RESULTS: Forty participants have been trained with the Tuebingen Thorax Trainer at our institution since November 2016. Thirty-five (87.5%) participants stated that the Tuebingen Thorax Trainer is an adequate model for VATS training. The ex vivo organ complex was reported to be realistic with regards to the level of detail and scale (76%). A large proportion of participants (27.5%) were experienced with VATS and reported having performed >50 procedures before taking the training course. CONCLUSIONS: This new training device allows realistic training for VATS procedures. 'Stagnant hydrostatic perfusion' permits simulation of reproducible bleeding scenarios. The device is low in production costs and offers a strong resemblance to the clinical scenario. It reduces the use of animal models and contributes to the efforts in making surgical skills training for VATS more accessible.